1997
DOI: 10.1021/ma970228f
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Adsorption of Poly(o-methoxyaniline) Self-Assembled Films

Abstract: The kinetics of adsorption of poly(o-methoxyaniline) (POMA) via self-assembly has been investigated using UV−vis spectroscopy. Though experimental conditions, including type of substrate, affect the amount of polymer adsorbed, adsorption of the first POMA layer on glass substrates was shown to occur in two stages, reaching saturation within a few minutes. The first stage is represented by a first-order kinetics with characteristic times of 5−10 s. The second stage also has an exponential behavior with t 1.5 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
147
1
9

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(178 citation statements)
references
References 17 publications
21
147
1
9
Order By: Relevance
“…The experimental procedures adopted for producing such SA lms have been described in ref. 18 , and therefore only a short description is given here. POMA was synthesized with ammonium peroxydisulfate in a 1.0 M HCl aqueous solution at 0 C. The monomer to oxidant ratio was 4:1.…”
Section: Multilayer Buildupmentioning
confidence: 99%
“…The experimental procedures adopted for producing such SA lms have been described in ref. 18 , and therefore only a short description is given here. POMA was synthesized with ammonium peroxydisulfate in a 1.0 M HCl aqueous solution at 0 C. The monomer to oxidant ratio was 4:1.…”
Section: Multilayer Buildupmentioning
confidence: 99%
“…Also, the shorter immersion time helps to prevent the competitive adsorption of water molecules, which in longer times would have more chance to attach to the substrate surface, reducing the number of sites for POEA adsorption. The water adsorption is very significant in these systems and according to the work done by Raposo et al 13 an energy is spent to remove water molecules from the substrate surface and to replace them by polymer chains. Besides, during the washing process both POEA and water molecules which are not very well adsorbed, are removed releasing sites for other molecules in a next immersion.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14][15] The predominant mechanism will depend on the pH of polymeric solution. In our previous work we have observed that in pH 3 the adsorption of poly(o-ethoxyaniline) on quartz is driven by electrostatic attraction due to the protonated nitrogen atoms; however, if the solution pH is increased to 5 hydrogen bonding becomes more important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Na literatura são encontradas dezenas de trabalhos que tratam do tema [18][19][20][21][22][23] , revelando que mecanismos genéricos ainda não podem ser propostos, uma vez que sistemas muito diferentes têm sido investigados. Em filmes formados por camadas de polieletrólitos, o processo de automontagem é governado por interações eletrostáticas entre seus grupos iônicos, levando à formação de pares iônicos 18 .…”
Section: Processos De Adsorção Em Filmes Automontadosunclassified